2003
DOI: 10.2320/matertrans.44.995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inclusion Particles on the Microstructure and Mechanical Properties of High Strength Austempered Ductile Iron

Abstract: Effects of inclusion particles on the microstructure and mechanical properties of high strength austempered ductile iron (ADI) were investigated in this study. Inclusion particles, especially when their sizes are less than 5 mm, were mostly found in intercellular regions. Whether an inclusion particle can induce the formation of acicular ferrite depends on Mn segregation. In intercellular region, acicular ferrite was hard to form in the vicinity of inclusion particles due to (1) serious Mn segregation, and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In general, the characteristics of non-metallic inclusions such as size, composition, morphology, and area/volume fractions are known to have an influence on the chemical and mechanical properties of alloys and steels [16,[26][27][28][29][30][31][32]37,61]. As the three HEAs in the present study have different impurity levels, the chemistry, size, and area fraction of the inclusion particles are subsequently different.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, the characteristics of non-metallic inclusions such as size, composition, morphology, and area/volume fractions are known to have an influence on the chemical and mechanical properties of alloys and steels [16,[26][27][28][29][30][31][32]37,61]. As the three HEAs in the present study have different impurity levels, the chemistry, size, and area fraction of the inclusion particles are subsequently different.…”
Section: Discussionmentioning
confidence: 98%
“…It is generally known that oxide particles that have a high hardness could deteriorate the mechanical properties of alloys such as failure and fatigue behavior. This is especially true for ductile metals such as austenitic steels and Ni alloys with an FCC crystal structure [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable example of such correlation is the Hall-Petch strengthening mechanism [13][14][15] in which there is negative correlation between the yield strength of a material and the square root of its' average grain size. Another example is the correlation between the nature and concentration of inclusions in some material to its' mechanical endurance under different loads, such as the under quasi-static loading 16,16,17 or fatigue (cyclic loading) 16,18 . The ability of a material to hold quasi-static The workflow of our proposed end-to-end system for quantitative metallography on a given input metal.…”
Section: Materials Science and Quantitative Metallographymentioning
confidence: 99%
“…However, in addition to the effect of the matrix grain size on the total elongation, there are other microstructural features that would also influence this property. For instance, it has been suggested that morphology and nature of the inclusions would affect the elongation of steels; the inclusions with good bonding to the matrix and/or with lower area fraction and more spherical shape are beneficial to the steel elongation [54,55]. The inclusions with sharp faceted shapes would provide the stress concentration and thus crack initiation centers, leading to premature failure which, in turn, would lower the elongation.…”
Section: Effects Of Re On the Tensile Behavior Of The Normalized Steelsmentioning
confidence: 99%